Heidegger's hidden sources : East Asian influences on his work - May, Reinhard (Routledge, 1996)
Heidegger's Hidden Sources documents for the first time Heidegger's remarkable debt to East Asian philosophy. In this groundbreaking study, Reinhard May shows conclusively that Martin Heidegger borrowed some of the major ideas of his philosophy - on occasion almost word for word - from German translations of Chinese Daoist and Zen Buddhist classics. The discovery of this astonishing appropriation of non-Western sources will have important consequences for future interpretations of Heidegger's work. Moreover, it shows Heidegger as a pioneer of comparative philosophy and transcultural thinking.